THE EFFECT OF PRODUCTION CAPACITY AND DESIGN OF OUTPUTS ON THE PERFORMANCE OF OPERATION - Baraka Bahjat Ahmed (Scholar Express Journals, 2025)
The efficiency of operational performance in manufacturing and service industries largely depends on production capacity and the design of outputs. This study explores the relationship between these factors and their impact on overall operational effectiveness. A well-optimized production capacity ensures resource utilization and cost efficiency, while a strategically designed output enhances product quality, customer satisfaction, and market competitiveness. Through a combination of theoretical analysis and case studies, this research highlights how aligning production capacity with output design can improve workflow, reduce bottlenecks, and enhance productivity. The findings suggest that businesses that integrate flexible capacity planning with innovative product design can achieve sustainable operational performance. This study provides insights for managers and industry professionals to refine their production strategies and improve overall efficiency
Keywords: Production capacity; ,Operational performance; Output design